CONTRIBUTION OF FAMILY ENVIRONMENT AND LEARNING WAYS AGAINST THE STUDENT LEARNING OUTCOMES GRADE X BUILDING GRAPHICS ON SUBJECTS IDENTIFY SCIENCE BUILDING AT SMK NEGERI 1 PARIAMAN - 867-887 , Ahmad Arif (CIVED, 2016)
ABSTRACTThe problems of this research were student learning outcomes grade X TGB in even semester 2015/2016 year in subjects “indentify science building” where at low level, there were 27.42% of students get value under the minimum clearance criteria (KKM). This study aims to describe the: 1) how large the contribution of family environment towards learning outcomes students, 2) how big contribution ways of learning against the student learning outcomes, 3) how large the contribution of family environment and ways of learning collectively against the results of student learning.     This research is descriptive research. The population of this research were grade X TGB SMK N 1 Pariaman. Sampele totaled 62 students were selected using total sampling techniques. The instrument used are the likert scale model. This data analyzed by the method of linear regression, product moment, simple regression, and double regression.     The findings of this research: 1) the level achievement of family environment on average in the less category, 2) the level achievement of ways of learning on average in the less category, 3) the level achievement of learning outcomes on average in the middle the category, 4) there are significant contributions family environment to wards learning outcomes students (r2 = 0.109), 5)there are significant contributions ways of learning to wards learning outcomes (r2 = 0.0101), 6) there are significant contributions family environment and ways of learning collectively against student learning outcomes (R = 0.117). Keywords: family environment, ways of learning,student learning outcomes